Synthetic CRISPR/Cas9 reagents facilitate genome editing and homology directed repair. Issue 7 (17th February 2020) - DiNapoli, Sara E; Martinez-McFaline, Raul; Gribbin, Caitlin K; Wrighton, Paul J; Balgobin, Courtney A; Nelson, Isabel; Leonard, Abigail; Maskin, Carolyn R; Shwartz, Arkadi; Quenzer, Eleanor D; Mailhiot, Darya; Kao, Clara; et al.
Abstract: CRISPR/Cas9 has become a powerful tool for genome editing in zebrafish that permits the rapid generation of loss of function mutations and the knock-in of specific alleles using DNA templates and homology directed repair (HDR). We examined the efficiency of synthetic, chemically modified gRNAs and demonstrate induction of indels and large genomic deletions in combination with recombinant Cas9 protein. We developed an in vivo genetic assay to measure HDR efficiency and we utilized this assay to test the effect of altering template design on HDR. Utilizing synthetic gRNAs and linear dsDNA templates, we successfully performed knock-in of fluorophores at multiple genomic loci and demonstrate transmission through the germline at high efficiency. We demonstrate that synthetic HDR templates can be used to knock-in bacterial nitroreductase ( ntr ) to facilitate lineage ablation of specific cell types. Collectively, our data demonstrate the utility of combining synthetic gRNAs and dsDNA templates to perform homology directed repair and genome editing in vivo .